2012
DOI: 10.2485/jhtb.21.481
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Bone Regeneration by Chitosan/Nanometer Hydroxyapatite/Collagen Composite Incorporating BMP-7 Mimetic Peptide

Abstract: The purpose of the present study was to examine whether the chitosan/ nanometer hydroxyapatite / collagen composite (chitosan/nHAC) incorporating BMP-7 mimetic peptide could accelerate bone regeneration. The chitosan/nHAC composite was prepared and the BMP-7 mimetic peptide introduced into the composite by vacuum adsorption. The released peptide content from the composite was detected using high performance liquid chromatography at different set times. 5 mm diameter cranial bone defects were created on both si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Importantly, this peptide exhibits higher osteogenic potential than BMP-7 [127]. Moreover, another BMP-7 mimetic peptide containing KQLNAISVLYFDD (Lys-Gln-Leu-Asn-Ala-Ile-Ser-Val-eu-Gln-Phe-Asp-Asp) amino acid sequence improves bone regeneration in vivo [128].…”
Section: Bmps-derived Peptidesmentioning
confidence: 99%
“…Importantly, this peptide exhibits higher osteogenic potential than BMP-7 [127]. Moreover, another BMP-7 mimetic peptide containing KQLNAISVLYFDD (Lys-Gln-Leu-Asn-Ala-Ile-Ser-Val-eu-Gln-Phe-Asp-Asp) amino acid sequence improves bone regeneration in vivo [128].…”
Section: Bmps-derived Peptidesmentioning
confidence: 99%
“…Draenert et al [21] had evaluated the biological effect of the growth factor [bone morphogenetic protein (BMP)] on human osteoblasts, which showed that sustained release of BMP on bone biomaterials had a stronger positive effect on biological scaffolds. Chitosan/nano-HA/collagen composite incorporating BMP was fabricated by Feng et al [22], successfully accelerating the healing of rat's cranial bone defects. In conclusion, the further research is much needed to incorporate BMP into FGM for promoting bone regeneration.…”
Section: Methodsmentioning
confidence: 99%
“…BMP-7-derived peptide (KQLNALSVLYFDD) containing 13 amino acids was built according to the literature (Fig. 1c ) 31 . BMP-7 and its derived peptide molecules were immersed in TIP3P water boxes and charges balanced with sodium and chloride ions.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…However, the structure of BMP-7 is complicated, it degrades easily in the body, and requires considerable time to be produced on a large scale. Thus, BMP-7-derived peptides have attracted attention because of their low-cost and excellent bio-functions 31 . Studies have shown that these peptides from the BMP-7 or BMP-7 receptors can be used to treat bone-related diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation